An attempt to measure the diametric relationship between slow and quick phases of nystagmus. (3rd July 2018) - Kanazawa, Yuji; Funabiki, Kazuo; Taura, Akiko; Imai, Takumi; Torii, Hiroko; Ogita, Hideaki; Okano, Takayuki; Ito, Juichi; Omori, Koichi
Abstract: Objective: To investigate whether our original method can precisely evaluate the angle between slow and quick phases of nystagmus (vector angle) and to determine whether vector angle analysis is helpful in differentiating between horizontal nystagmus and mixed nystagmus with horizontal and vertical components. Methods: We included 20 healthy volunteers, 17 patients with horizontal nystagmus, and 15 patients with mixed nystagmus. Caloric nystagmus was recorded in healthy volunteers; positional nystagmus was recorded in each patient. We extracted the velocity of nystagmus from eye movement of each subject and analysed the vector angle. Results: In caloric nystagmus, the vector angle approached 180 degrees as slow-phase velocity increased, suggesting that our vector angle measurement is more reliable with faster nystagmus. Importantly, in horizontal nystagmus from peripheral vestibular disease, the vector angle similarly approached 180 degrees as slow-phase velocity increased; in contrast, the vector angle in cases of mixed nystagmus from vertebrobasilar insufficiency or spinocerebellar degeneration significantly differed from the angle of caloric nystagmus. Conclusions: Vector angle analysis using our original algorithm can precisely evaluate the diametric relationship in vestibular nystagmus; it may be helpful in diagnosis of non-peripheral vestibular disorders.